Development of material training of infographic video using adobe premiere cs6 in nonformal education - Rusli, Mulyadi; Rini, Faiza; Jasmir, Jasmir; Latief, Suryawahyuni; Fun, Chi-Win (Journal of Nonformal Education, 2023)
The perkumpulan alam hijau (A-HI) is a form of non-formal education that organizes various training activities and is located in Jambi City.  One form of training held is infographic video-making training. So far, the training activities given to students are the delivery of material through power points. The final results of the training activities provided by delivering material through power points are not optimal. Therefore, it is necessary to carry out media development solutions in the delivery of training materials using adobe flash premiere cs6. This study aims to develop a medium for delivering material for making infographic videos based on adobe premiere cs6 using the analysis, design, development, implementation, and evaluation (ADDIE) model. The results showed that the training material for making infographic videos using adobe premiere cs6 was effective as shown by the results of an assessment conducted by multimedia experts based on three aspects, namely display, operation, and interaction. The percentage of the results of the assessment of the three aspects is 91%, with the highest percentage being in the operational aspect at 93% and followed successively by the interaction aspect (92.20%), and the display aspect at 87.40%.  Meanwhile, the assessment carried out by the training participants was seen from four aspects, namely benefits, appearance, interaction, and independent learning. The percentage of the four aspects of an assessment is 88.10% with the largest percentage being in the interaction aspect, which is 92% and the lowest percentage is in the independent learning aspect, which is 80%.